IDENTIFICATION AND CHARACTERIZATION OF 25 MICRORNAs AND THEIR TARGETED PROTEINS IN APRICOT (PrunusarmeniacaL.) - I. A.Baloch; M. Y. K. Barozai; M. Din (Journal of Animal and Plant Sciences, 2015)
MicroRNAs (miRNAs) are non-protein codingregulatory RNAs. These are small and endogenous in nature. Their length ranges from 18-26 nucleotides (nt) and show conserved nature in plants. The conserved nature of miRNAs becomes a logical approach for the hunt of new miRNAs in other organisms by comparativegenomics. ThemiRNAs are reported in large number of plants but very limited number is reported in an important fruit; apricot (Prunusarmeniaca L.) The current study dealt with the identification and characterization of miRNAs and their targeted proteins in apricot. Consequently 25 miRNAs belonging to 24 miRNA families were identified and characterized in Prunusarmeniaca. All of the identified miRNA families (miR-159, 160, 162,164,166, 167, 172, 390, 393, 394, 395, 396, 408, 477, 482, 535, 3627, 6034, 6266, 6271, 6286, 6482, 6485 and 8123) are being reported for the first time in Prunusarmenica. The precursor-miRNAs lengths of newly identified miRNAs range from 51 to 238 nt with an average of 120 nt. The mature miRNA sequences length rang from 20 to 23 nt.A total 33 putative targets for the apricotmiRNAs have also been identified. These targets are the significant proteins including transcription factors. Identification of 25 miRNAs and their targeted proteins will be helpful to understand and manage the gene regulation in Prunusarmeniaca.
Keywords: Comparative genomics; Gene regulation; microRNAs; Prunusarmeniaca